Effects of spaces, electronic devices, and basic services available on households during COVID-19 confinement: A study in the Dominican Republic - García Frómeta, Yokasta; Cruz Pichardo, Ivanovnna Milqueya; Rojas Cortorreal, Gilkauris (Entrópico Arquitectura y Urbanismo, 2023)
The daily lives of the world population were impacted and went into crisis mode due to the COVID-19 pandemic, which, as of November 2019, has taken over us. The changes in everyday behavior have generated consequences in all aspects of life hindering the labor, education, and recreational sectors. The COVID-19 pandemic has led us to analyze and rethink relevant or predominant factors for choosing a home. The workplace, location of the best schools, safety, and economic aspects are of great influence when it comes to choosing a home. During this past year, not all of these factors played a role since we have been forced to continue with all of our activities from home. But what happened to the population that did not consider space, ventilation, and even access to fresh air or recreation when choosing their home? Where the economic factor, as well as access to work and/or school environments, have always prevailed. With this in mind, a survey was performed in the Dominican Republic with the intent of discovering the effects of spaces, electronic devices, and access to basic services during the COVID-19 pandemic, which are crucial for current telecommuting and distance learning processes.